Attitudes towards Religion, Religious Institutions and Ethics Motivated Religiously - Czerniawska, Mirosława (INSTED: Interdisciplinary Studies in Education & Society, 2018)
The main aim of this research is a diagnosis of attitudes towards religion, religious institutions (theirrole in public sphere of social functioning), ethics motivated religiously and systems of values. The sam-ple consists of 368 students. It has been assumed that attitudes depend on a system of values and a variation on ?conservatism and openness to change? dimension. The theoretical framework is based on theconcept of S.H. Schwartz and his Portrait Values Questionnaire (PVQ) has been used. In order to meas-ure attitudes a dedicated tool has been constructed. The obtained results give grounds to confirm thehypothesis. Positive attitudes towards the discussed matter are linked to the higher acceptance of the?conservative? value, especially of the following types:: ?humility?, ?tradition?, and ?conformity rules?.Negative attitudes are linked to the higher acceptance of the ?openness to change? value, especially of thefollowing types: ?self-direction-thought?, ?self-direction-action? and ?stimulation?. The difference be-tween these value types are not statistically significant for every analysed attitude.